COMMUNITY SERVICE EDUCATION FOR EARLY DETECTION OF HIGH RISK OF PREGNANT WOMEN BASED ON HEALTHY TRADITIONS AT SALLY'S CLINIC - Deni Irawati; Herlina; Angel Kristiani Zai (Cattleya Darmaya Fortuna, 2024)
The Maternal Mortality Rate (MMR) is still the main indicator of the success of health development in Indonesia. One of the main challenges is the delay in early detection of pregnancy complications that are exacerbated by inaccuracies in traditional perceptions or myths in society. This community service activity aims to increase the knowledge, awareness, and independence of pregnant women in conducting early detection of high risk of pregnancy through the